Inkorporasi Ekstrak Daun Jarak Pagar (Jatropha Curcas L) dalam Patch Transdermal Sebagai Anti Hiperglikemi; Formulasi Dan Pankreatik Histopatologi - Sukmawati, Muli; Arisanty; Daswi, Dwi Rachmawaty; Stevani, Hendra; Daton, Dicky Alexander (Media Farmasi, 2024)
Incorporation Of Jarak Pagar Leaves Extract (Jatropha Curcas L) In Transdermal Patch As Antihyperglycemic ; Formulation And Pancreatic Histopathology Transdermal patches are known to have a more immediate therapeutic effect and could avoid the risk of side effects that may arise compared to oral. This study aimed to produce Jarak Pagar leaves ethanolic extract transdermal patch (JPL-EETP) to enhance the penetration of Jarak Pagar leaves extract (JPL-EE) to maximize the systemic therapeutic effect of antidiabetics. In addition, easy and enjoyable medication could improve patient compliance. Transdermal patch was prepared by making the formula of JPL-EETP with different concentrations of extract with solvent-evaporated methods. JPL-EETP optimization was carried out by determining the pH, aeration, folding resistance, and organoleptic. Furthermore, the optimal JPL-EETP formulas were followed by the in vivo assay, ex vivo assay, and pancreatic histopathology assay. The JPL-EETP physicall determination were carried out the appropriate of transdermal patch measurements.  F3 with an JPL-EE concentration of 1.75 g can provide an antidiabetic effect on in vivo asay that is as good as oral antihyperglycemic drugs (p>0.05). Ex vivo study confirmed that the gallate acid permeation across the porcine skin of F2 showed higher percentage of permeation of 94,2% respectively after 24 h. The histophatology assay presence no significant difference between the surface area of ​​the islets of Langerhans and the histopathological after administration of metformin or Jarak Pagar leaves extract transdermal patch. The results suggest that Jarak Pagar leaves ethanolic extract transdermal patch is a potential candidate of antidiabetics drug from natural source and can provide a higher patient compliance along with effectiveness in the management and treatment of diabetes which can be easily applied to the skin. Sediaan patch transdermal diketahui memiliki efek terapi yang lebih cepat dan dapat amenghindari resiko efek samping yang mungkin timbul dibanding sediaan oral. Penelitian ini bertujuan untuk membuat ekstrak etanol daun Jarak Pagar (PT-EJPL) yang diformulasikan dalam bentuk patch transdermal untuk meningkatkan efektifitasnya sebagai antihiperglikemi. Patch transdermal dibuat dalam beberapa konsentrasi EJPL dengan metode solvent-evaporated. Karakteristik PT-EJPL ditentukan dengan pengukuran pH, daya lipat, dan uji organoleptik. Penentuan efek antihiperglikemi dilakukan secara in vivo menggunakan tikus wistar putih. Persentase pelepasan fenolik dilakukan secara ex vivo menggunakan kulit babi selama 24 jam. Analisis pakreas histopatologi dilakukan dengan melihat luar area pulau langerhans sebelum dan sesudah perlakuan. Hasil pengujian menunjukkan karateristik patch yang sesuai persyaratan. Formula 3 dengan konsentrasi EEJPL 1.75 g menunjukkan efek antihiperglikemi pakling baik (p<0.05) sejalan dengan hasil uji pelepasan asam gallat pada F3 mencapai 94,2% pada jam ke 24. Analisis histopatologi luas permukaan sel langerhans menunjukkan tidak perbedaan signifikan antara kelompok kontrol dan perlakuan (p>0.05). Penelitian ini berhasil memformulasikan EJPL kedalam sistem penghantaran transdermal dan dapat dipertimbangkan sebagai kandidat antidiabetik herbal.